The effect of new cultural phenomenon’s оn a transformation of a psychoculture of the personality - Ардашова, Я. І. (Proceedings of the National Aviation University Series Philosophy Cultural, 2016)
Disclosed the features of the emergence and formation of new cultural phenomena. It was shown of the effect of cultural phenomenon’s оn a transformation of a psychoculture of the personality in the information age.